Pengembangan Model dan Strategi Reformasi Birokrasi Yang Berorientasi Pada Pelayanan Publik Untuk Mewujudkan Good Governance di Daerah - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Susi Ratnawati (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Bureaucracy of regional government in reformation era is demanded to affors in creating clean and good, transparency, responsive, efficient and effective government as well. The demand is increasingly avoidable by public distrust because of KKN (Corruption, Collution, Nepotism) practice in government bureaucracy wich is increasingly systemic and privade to areas of region. Bureaucracy reformation is the needy wich capable to lessen KKN practical, it is, however in appropriate if phenomena tern only in administrative technigues. Public servant status must be put to have main role from government bureaucracy to create good local governance. This study want to examine comprehensively how bureaucracy of government to increase public servant in the framework of good local governance and review the factors of causality relationship as well which influence either bureaucracy internal or external so it able to create clean and accountable in regions. The result from the study is : The development of participatory bureaucracy reformation model and equality wich oriented to public service. Among other creative, innovative and proactive public servant, low cost administration and easy license, transparency cost, fast and easily accessible, society as locust (citizen charter)